The Portuguese Severe Asthma Registry: Development, Features, and Data Sharing Policies. (21st November 2018) - Sá-Sousa, Ana; Fonseca, João Almeida; Pereira, Ana Margarida; Ferreira, Ana; Arrobas, Ana; Mendes, Ana; Drummond, Marta; Videira, Wanda; Costa, Tiago; Farinha, Pedro; Soares, José; Rocha, Pedro; et al.
Abstract : The Portuguese Severe Asthma Registry ( Registo de Asma Grave Portugal, RAG) was developed by an open collaborative network of asthma specialists. RAG collects data from adults and pediatric severe asthma patients that despite treatment optimization and adequate management of comorbidities require step 4/5 treatment according to GINA recommendations. In this paper, we describe the development and implementation of RAG, its features, and data sharing policies. The contents and structure of RAG were defined in a multistep consensus process. A pilot version was pretested and iteratively improved. The selection of data elements for RAG considered other severe asthma registries, aiming at characterizing the patient's clinical status whilst avoiding overloading the standard workflow of the clinical appointment. Features of RAG include automatic assessment of eligibility, easy data input, and exportable data in natural language that can be pasted directly in patients' electronic health record and security features to enable data sharing (among researchers and with other international databases) without compromising patients' confidentiality. RAG is a national web-based disease registry of severe asthma patients, available at asmagrave.pt . It allows prospective clinical data collection, promotes standardized care and collaborative clinical research, and may contribute to inform evidence-based healthcare policies for severe asthma.